The effectiveness of the traditional Tapo' Pipit game in stimulating aspects of child development - Halida, Halida; Lukmanulhakim; Ariyani Ramadhani; Fifi Khoirul Fitriyah (Jurnal Pendidikan Anak, 2025)
This research was motivated by the rapid development of technology which makes children more attracted to digital games. Moreover, change of life style and modern parenting cause children spend more time only at home and have less opportunity to interact to traditional games. This research was aimed to measure and analyze the effectiveness of Tapo’ Pipit traditional game in stimulating aspect of early age children development. This research used a quantitative descriptive approach with a one-group pretest-posttest design. Research subject was 22 children of Primanda Kindergarten, Pontianak. The intervention was conducted for 6 meetings with a duration of 60 minutes. The data collection technique used observation on children. Analysis descriptive was used as data analysis, and hypothesis was tested by using pair t-test. The result of this research shows that Tapo’ Pipit Traditional Game can stimulate aspect of chilren development. The contribution of this research was Tapo’ Pipit traditional game is an learning model that is interested to be introduced early age children.